(untitled) (Journal of Oriental Studies, 2016)
The article is dedicated to the topic of “babu-l-harf” in “Sharhu-l-Unmuzaj fi-n-nahv” of distinguished Azerbaijani arabic linguist Jamaleddin Muhammed ibn Abdulghani al Ardabili who lived in the end of XII and in the first half of XIII centures. In order to bring some explanation to grammatical problems there were mentioned works of classic linguists as Halil Ibn Ahmad, Ferra and Sebaweyh in the article. This article is very important from viewpoint of research of nearly eight centures old resourse and investigation of conditions of Azerbaijani linguistic science in Middle Ages, also revealment of that period’s linguists’ importance in the development of Arabic linguistics.